1098 Title-Sound Induced Drop Attacks, is it cataplexy or seizure?. (27th April 2018) - Kulsum, Umma; Gupta, Divya; Ma, Wei; Polos, Peter; Shah, Bankim
Abstract: Introduction: Drop attacks due to cataplexy are usually triggered by laughter, surprise or other emotions. Atonic seizures consist of a spontaneous brief lapse in muscle tone, usually lasting < 15 sec. Report of Case: A 55 year old female had sleepiness, and multiple falls for 4 years but occurring more frequently in the last few months. Mostly, these "drop attacks" were related to hearing a loud sound (e.g. screaming), but not to any emotional situations. Sometimes, she could feel that it is coming. She was on treatment for "vestibular migraines" with Celebrex, Klonopin, Topiramate, Meclizine, prescribed by her neurologist. She was referred to the sleep clinic to rule out narcolepsy with cataplexy. Patient was found to have symptoms of snoring, severely elevated Epworth sleepiness scale sore of 16/24. She did not have sleep paralysis, hypnagogic hallucinations, automatic behaviors or parasomnias. Her systemic and neurological examinations were normal. PSG+MSLT was done after holding Klonopin and Topiramate for 2 weeks. Her PSG showed Moderate OSA with apnea +hypopnea index of 21.3/hour. In the Bipolar array of EEG, it showed recurrent left central sharp waves (at C3) during sleep and less often in wakefulness. Her MSLT showed a mean sleep latency of 5.8 mins suggestive of hypersomnolence, but did not show SOREMP's. She had also been referred for an ambulatory EEG which showed recurrent left temporal sharp waves during sleep. Conclusion: Therefore, it appears that her drop attacks could be from seizures and her hypersomnolence, due to underlying OSA. Further evaluation is ongoing by epileptologist. Autosomal dominant partial epilepsy with auditory features (ADPEAF) is rare conditions with simple partial seizures, that may be triggered by specific sounds, and likely arise in the lateral temporal lobe. Addition of bi-temporal electrodes in the standard EEG montage for PSG recording will help to better differentiate cataplexy vs seizure.